Theatre, Science, and the Popular: Two Contemporary Examples From Scandinavia - Skjoldager-Nielsen, Daria; Skjoldager-Nielsen, Kim (Nordic Theatre Studies, 2018)
This article explores relations between theatre, science, and the popular, which have largely been overlooked by Nordic theatre studies. The aim here is to introduce and understand the variety of ways theatre may communicate science to the public, the point of departure informed by the historical development of the relations between the three concepts and Edmund Husserl’s phenomenological critique of modern science. The two analytical examples are Swedish Charlotte Engelkes’ and Peder Bjurman’s Svarta hål – en kvantfysisk vaudeville (2014) and Danish Hotel Pro Forma’s adult performance for children Kosmos+ En Big Bang forestilling om universets vidundre (2014). History of science reveals complex combinations of science and the popular in theatrical events that raises the question if the audience’s understanding of the scientific subject matter itself always was – or has to be – the purpose of the popular science performance, or if it rather was – and is – about spurring interest by inspiring sentiments of wonder and reflection on science’s impact on life and outlooks. Newer conceptual developments also suggest that it is not always the case that theatre is a tool for science popularisation, as a specific genre science theatre, but that scientific information and concepts are artistically interpreted by theatre, and not always in ways affirmative of the science. This later variant is called science-in-theatre. The two genres are demonstrated through the analyses of Svarta hål and Kosmos+, the claim being that the first was an ambiguous exposition of science, i.e. science-in-theatre, whereas the second established an artistically visionary affirmation, as regular science theatre.